Digital Forensic and Methods: A Decade in Review - Safari, Ferdi; Phahlevy, Rifqi Ridlo; Fiddina, Irta (Proceedings of The ICECRS, 2023)
This study examines a decade of digital forensic research using data from lens.org, focusing on "Digital Forensic" and "Methods." The dataset, rigorously filtered for Scholarly Works, reveals key trends: the University of Worcester as a prolific contributor (2 articles), a publication peak between 2010-2011 (15 articles), and Computer Science dominating with 65 articles. Concordia University Wisconsin emerges as active, publishing 2 articles, with Ameir Hossein Taherinia as a standout author (3 publications). Notably, the seminal work "An Automated Timeline Reconstruction Approach for Digital Forensic Investigations" garnered 100 citations. The United States leads in activity (18 articles), with Inderscience Publishers notably featuring in the "International Journal of Electronic Security and Digital Forensics" (24 articles). This dataset lays a vital foundation for future research in digital forensics and methods. Highlights : Examination of a decade of digital forensic research Reveals prolific contributors, notable publications, and leading authors Provides a foundational resource for future digital forensic studies Keywords: Digital Forensic, Methods, Scholarly Works, Publication Trends